(untitled) (Journal of the College of Basic Education, 2022)
Clostridium difficile infection (CDI) has become a significant threat to public health. Although broad-spectrum antibiotic therapy is the primary treatment option for CDI, its use has evident limitations. Probiotics have been proved to be effective in the treatment of CDI and are a promising therapeutic option for CDI. In this study, strain of Saccharomyces boulardii was evaluated for their anti-C.difficile activity. The antibacterial activity of the standard isolated yeasts (biocodex, France) against pathogenic bacteria C. difficile in vitro was determined by Well’s Diffusion method, the isolated yeast showed antibacterial activity against tested bacterium, the highest diameter of inhibition zone was (11 mm) . The study aimed to use the yeast Saccharomyces boulardii as probiotic for the prevention and treatment of diarrhea and colitis associated with antibiotics .These results may provide a basis for alternative therapies for the treatment of C. difficile-associated gut disorders.